2000
DOI: 10.1016/s0028-3932(99)00050-0
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric transfer of colour and shape information in the presence and absence of the corpus callosum

Abstract: Two split-brained subjects, one (L.B.) with full forebrain commissurotomy and one (R.B.) with callosal agenesis, and a group of twenty neurologically intact subjects were tested in three discrimination tasks: a go±no go task, a two-choice task, and a three-choice task. The discriminations were based on colour in Experiment 1, and on shape in Experiment 2. The stimuli were presented in one or other visual ®eld, and the subjects responded with the ®ngers of one or other hand, allowing the di erences in reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Second, all stages are concurrently active: Their activation is continuously passed on from stage to stage such that the increase of activation at a given stage is proportional to the difference between its current activation and the activation of the immediately preceding stage. Thus, the cascade model pictures the flow of information as a continuous wave of activation traveling along successive discrete processing stages, a notion that has proven especially influential in the area of cognitive psychophysiology (e.g., Forster & Corballis, 2000;Scheffers & Coles, 2000). Also, it is one of relatively few models assuming partially overlapping processing stages that are sufficiently specified to allow derivation of explicit quantitative predictions (Schweickert & Mounts, 1998;Ulrich, Mattes, & Miller, 1999).…”
Section: Mixture Models and Their Delta Plotsmentioning
confidence: 99%
“…Second, all stages are concurrently active: Their activation is continuously passed on from stage to stage such that the increase of activation at a given stage is proportional to the difference between its current activation and the activation of the immediately preceding stage. Thus, the cascade model pictures the flow of information as a continuous wave of activation traveling along successive discrete processing stages, a notion that has proven especially influential in the area of cognitive psychophysiology (e.g., Forster & Corballis, 2000;Scheffers & Coles, 2000). Also, it is one of relatively few models assuming partially overlapping processing stages that are sufficiently specified to allow derivation of explicit quantitative predictions (Schweickert & Mounts, 1998;Ulrich, Mattes, & Miller, 1999).…”
Section: Mixture Models and Their Delta Plotsmentioning
confidence: 99%
“…Hanajima et al (2001) found that muscle responses to transcranial stimulation over the left-hand motor cortex can be facilitated when transcranial stimulation has been applied 4–5 ms earlier over the right-hand motor cortex, about the same time as the CUD value estimated from behavioral studies in normal subjects. In acallosal and commissurotomized patients the CUD is prolonged (~30–70 ms) because of longer reaction times to lateralized stimuli in the crossed compared to the uncrossed condition owing to the indirect route required for interhemispheric transfer (e.g., Berlucchi et al 1971; Berlucchi et al 1995; Clarke and Zaidel 1989; Forster and Corballis 1998, 2000). …”
Section: The Role Of the CC For The Integration Of Lower-level Functionsmentioning
confidence: 99%
“…A possible neural mechanism for facilitation and interference between global and local processing levels involves interhemispheric interactions (Corballis et al, 2004;Forster and Corballis, 2000). Evidence from a split-brain study (Robertson et al, 1993) suggests that the corpus callosum mediates local-global interference.…”
Section: The Role Of the Corpus Callosum In Interference And Facilitamentioning
confidence: 99%